2004
DOI: 10.1007/s10484-004-0386-1
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Results of Psychophysiological Stress Profile in Functional Somatic Syndrome: Correlation Between Subjective Tension Score and Objective Stress Response

Abstract: Mind-body interactions are important in functional somatic syndromes (FSS). Therefore, in the assessment of the psychophysiological stress response in patients with FSS, both subjective feelings and psychophysiological activity should be simultaneously measured. In this study, "Objective Tension Score" (OTS) was defined as an objective parameter of tension; it consisted of surface electromyography and skin conductance level as indicators of muscle and mental tension, respectively. "Subjective Tension Score" (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 26 publications
3
18
0
Order By: Relevance
“…These results may indicate that RFB produced on the one hand calmness to cope with daily stress and on the other hand improvement of body awareness. This is in line with the general finding that clinical biofeedback and selfregulation treatment increases body awareness and awareness of psychological-somatic interrelationships (Cohen and Sedlack 1983;Kanbara et al 2004). Wickramasekera (1999) reported that people with high scores in trait hypnotic ability would profit most from biofeedback by rapidly reducing clinical symptoms.…”
Section: Discussionsupporting
confidence: 71%
“…These results may indicate that RFB produced on the one hand calmness to cope with daily stress and on the other hand improvement of body awareness. This is in line with the general finding that clinical biofeedback and selfregulation treatment increases body awareness and awareness of psychological-somatic interrelationships (Cohen and Sedlack 1983;Kanbara et al 2004). Wickramasekera (1999) reported that people with high scores in trait hypnotic ability would profit most from biofeedback by rapidly reducing clinical symptoms.…”
Section: Discussionsupporting
confidence: 71%
“…Okifuji and Turk (2002) investigated the relation between pain in FMS and autonomic nervous system function, and suggested that FMS is a prevalent muscloskeletal pain disorder characterized by diffuse pain, in which the patient develops dysfunctional sympathetic reflexes to stressors. In our previous report, SEMG level and SCL were significantly hypo-reactive to a stress task in FSS (Kanbara et al, 2004). In the present study, we investigated the relations among SEMG level, TEMP and SCL in FMS patients.…”
Section: Introductionmentioning
confidence: 73%
“…Thus, the symptoms represent both somatoform and dissociative qualities. In parallel with the concept of alexithymia (lack of ability to feel or express emotions), we would like to support the introduction of the concept of alexisomia in this field [30], as these women, in many ways, lack a normal quality of sensations (exteroceptive and proprioceptive) and the ability to express themselves in a functionally normal body language.…”
Section: Diagnosis Of Cpp In the International Classification Of Disementioning
confidence: 97%